Organisational commitment and organisational cynicism as feedback signals: from zero to substantive CSR - Vveinhardt, Jolita (Business: Theory and Practice, 2024)
Corporate social responsibility (CSR) declared by organisations can be understood as a specific signal sent to stakeholders. However, social responsibility can vary from its complete absence to symbolic or substantive CSR. There is still a lack of knowledge on how employee feedback, manifesting itself by organisational commitment or organisational cynicism, varies depending on the nature of CSR and employee seniority. Therefore, this exploratory study examines how organisational cynicism and organisational commitment manifest themselves in organisations in different situations with regard to CSR. The study was conducted in Lithuania, surveying 981 employees from public and private sector enterprises. Organisations are divided into three groups showing the corresponding level of social responsibility: substantive, symbolic and not CSR. Organisational commitment was tested using two different instruments: Organisational Commitment Questionnaire (OCQ) by Mowday et al. (1979) and an instrument created by Allen and Meyer (1990). Organisational commitment (as in the cases of affective, continuance and normative commitment) was the strongest in the substantive CSR group; and the weakest, in the not CSR group. Employee cynicism showed the opposite result. The same consistency was observed separately in the public and private sectors, with stronger commitment and weaker cynicism found in the public sector. Organisational commitment and cynicism demonstrated by employees emerge as reactions to corporate social responsibility and as a kind of feedback signal sent to persons responsible for organisational management. The results are discussed considering the signalling theory, and their implications for practice are highlighted.